Analisis Kepuasan Pengguna Terhadap Layanan Gofood Menggunakan Metode End User Computing Satisfaction - Aprillia, Nazwa; Sanjaya, M. Rudi (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Gofood is an online food delivery service provided by Gojek application, which was the greatest online food delivery service in Indonesia in 2019, but it has fallen to the second position behind Grabfood in the last three years with a diminishing market share. The goal of this study was to perceive Gofood user satisfaction through the EUCS method, which would assess the impact of content, accuracy, format, ease of use and timeliness variables on the satisfaction variable. This study included 370 students from Sriwijaya University’s Computer Science Faculty. According to the results, the t-value of content, format, ease of use and timeliness variables is greater than 1,967 and the significance value < 0,05 explaining that these four variables have a significant effect on the satisfaction variable, so the conclusion is the users are satisfied by these four variables in Gofood services. Meanwhile, the t-value of the accuracy variable is 1,492 < 1,967 and the significance value is 0,137> 0,05, indicating that it has no significant effect on the satisfaction variable and should be improved or optimized.